Pengaruh Perbedaan Lama Perendaman dalam Larutan Pupuk Fosfat Terhadap Pertumbuhan Rumput Laut Gracilaria verrucosa (Hudson) Papenfuss Di Pertambakan Desa Wonorejo, Kaliwungu-Kendal - Sari, Ayu Permana; Sunaryo, Sunaryo; Djunaedi, Ali (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Species G. verrucosa is naturally harvested, through harvesting and retrieval in nature. These activities led to excessive exploitation and dangerous continueties of seaweed population. There for it would require an effort to increase the production of G. verrucosa, including through aquaculture cultivation in area with good land management and proper use of fertilizer. One of the problems in the evironmental factors that affect production of G. verrucosa is limited nutrients. This problem can be solved by ensuring availability of nutrients. Added of inorganic elements for alternative to achieve an optimal level of production. The research design was Completely Randomized Design (CRD) with immersion time difference in G. verrucosa using SP 36 fertilizer. The immersion treatments were: A. control, B. 10 minutes, C. 20 minutes, D. 30 minutes, E. 40 minutes, F. 50 minutes, G. 60 minutes. This study used P (phospat) obtained from SP 36 fertilizer with concentration 0,2 g/L. Plantation was done by using a longline method of 72 ties and mantained for 35 days. The result show that the immersion period of G. verrucosa significantly effect (p<0,01), on the growth of G. verrucosa. This can be seen from the highest average specific growth rate of G. verrucosa in the treatment G (2,36 % per day) and the lowest average specific growth rate G. verrucosa in treatment A (1,14 % per day).